The Challenges Faced by Christian Missionaries and Maranao Muslims in Lanao del Sur, Marawi City: A Scientific Study - Mohammad Nashief S. Disomimba (Asian Journal of Philosophy and Religion, 2022)
This paper utilized a content study to clarify the several challenges faced by Maranao Muslims in the Province of Lanao del Sur, Marawi city. The study focuses on the following activities conducted by Prelature Sisters in Marawi city, Parish in Balabagan, and in Malabang mentioning their challenges both Maranao Muslims and Christian missionaries. The tendency of giving priority of this study is to discuss the challenges faced by Christian Missionaries and Maranao Muslims in Lanao del Sur, Marawi city, to clarify the hidden reality of their challenges. To address this limitation, an analytical study is conceived to foreground the challenges of Christianization in the Province of Lanao del Sur.Descriptive Analysis used in this paper in  order to describe the challenges faced by Christian Missionaries and Maranao Muslims, contextualizing and examining the factors that shaped challenges, synthesizing and understanding/confirming/clarifying the reality of challenges. One of the most important result of the study; the Filipino Muslims knew that the main purpose of existing of the Christian missionaries and Christian settlers in their areas through the Philippine Government is to Christianize them. The challenges faced by Maranao Muslims taught them to wake-up each other, and taught them to unite in order to stop the Christianization in the province of Lanao del Sur, and the Christianization program never success in Marawi City until now.